Global Dynamics of Visual Literacy Scholarship in Higher Education: Insights from a Bibliometric Analysis - Dio Lingga Purwodani; Dwi Soca Baskara; Nabil Muttaqin (ITScience (Information Technology and Science), 2025)
Visual literacy has become a central competency in higher education as digital and multimodal communication increasingly shapes learning practices. Although its pedagogical relevance has been widely recognized, existing research remains fragmented and lacks a comprehensive global mapping of how visual literacy scholarship has evolved—particularly in terms of intellectual structure, collaboration patterns, and thematic development. This study employs a bibliometric approach to analyze global research trends on visual literacy in higher education using Scopus-indexed publications from 2019 to 2024. Bibliometric indicators related to publication growth, productivity, citation impact, and international collaboration were examined using RStudio (Bibliometrix) and VOSviewer. Findings show a significant rise in publication output, with more than 177 documents published in 2024—representing the highest annual growth within the examined period. Indonesia, particularly through Universitas Pendidikan Indonesia, shows strong research productivity, followed by Texas Tech University and the University of Nevada. Despite increasing contributions from Asian and Western institutions, international collaboration remains limited, especially among Southeast Asian universities. This study demonstrates that visual literacy has developed into an increasingly dynamic and interdisciplinary research field. The novel contribution of this study lies in offering the first comprehensive, data-driven global mapping of visual literacy scholarship in higher education, revealing its publication dynamics, collaborative structures, and emerging thematic directions. Strengthening international partnerships is essential for advancing theoretical development and pedagogical innovation in visual literacy research.